Post-harvest storage of ‘Paluma’ guavas produced by plants fertirrigated with nitrogen and biofertilizer - Santana, Elisson Alves; Lima, Deisiele Diniz; Souza, Clériton; Neto, Acácio Figueiredo; Cavalcante, Ítalo Herbert Lucena; de Sousa, Karla dos Santos Melo (Comunicata Scientiae, 2020)
The association between mineral fertilizer and biofertilizers can contribute to guavas quality. An experiment was carried out in order to assess, over the days, 'Paluma' guavas physical-chemical quality in function of nitrogen fertilizer and biofertilizer doses. It was adopted a randomized blocks with treatments distributed in a factorial 5 x 2 x 5 referring to evaluation days post-harvest (0, 3, 6, 9 and 12), nitrogen fertilization (50 and 100% culture recommendation) and application of bovine biofertilizer doses by fertigation (0.0, 2.5, 5.0, 7.5 and 10.0%). The physical-chemical quality of 'Paluma' guava fruit was influenced by the association between liquid bovine biofertilizer and nitrogen fertilization. This combination increased soluble solids, titratable acidity, ratio, vitamin C, pH, firmness and loss of fresh mass, but did not affect the pulp percentage. The bovine biofertilizer, together with mineral fertilization, is important to increase the post-harvest quality of 'Paluma' guava.